2007
DOI: 10.1124/jpet.107.125500
|View full text |Cite
|
Sign up to set email alerts
|

A Select Set of Opioid Ligands Induce Up-Regulation by Promoting the Maturation and Stability of the Rat κ-Opioid Receptor in Human Embryonic Kidney 293 Cells

Abstract: Ligand-induced regulation of the rat -opioid receptor (rKOR) was investigated in human embryonic kidney 293 cells stably expressing the FLAG-tagged rKOR. Incubation of rKOR cells with naltrexone for 24 h increased the B max Ͼ3-fold, with no change in the affinity of [ 3 H]diprenorphine. Two immunoreactive receptor species were present in cell lysates: naltrexone treatment caused a Ͼ3-fold increase in the 52-kDa species while decreasing the level of the 42-kDa species. Dynorphin(1-13), U69,593]pyran-7-carboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The ultracentrifugal supernatant, containing approximately 300 mg of solubilized membrane protein, was incubated with WGA agarose beads to enrich the 52 kDa mature form of rKOR. We have shown previously that the 42 kDa does not bind efficiently to WGA (Wannemacher et al, 2007). Aliquots (0.03% v/v) of the WGA-agarose input, flow-through fraction and N-acetylglucosamine eluate were resolved using SDS/PAGE to assess the effectiveness of the lectin chromatography to purify the receptor.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The ultracentrifugal supernatant, containing approximately 300 mg of solubilized membrane protein, was incubated with WGA agarose beads to enrich the 52 kDa mature form of rKOR. We have shown previously that the 42 kDa does not bind efficiently to WGA (Wannemacher et al, 2007). Aliquots (0.03% v/v) of the WGA-agarose input, flow-through fraction and N-acetylglucosamine eluate were resolved using SDS/PAGE to assess the effectiveness of the lectin chromatography to purify the receptor.…”
Section: Resultsmentioning
confidence: 93%
“…Surprisingly, chronic agonist treatment leads to receptor down-regulation in the case of the human, but not the mouse or rat KOR (Zhang et al, 2002; Chen et al, 2006; Wannemacher et al, 2007). The carboxyl terminus of the receptor is believed to contribute towards the species variation (Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Though this may be the first instance of agonist-caused upregulation of MOPr in cell culture, this phenomenon has been observed with other GPCRs, including the kappa opioid receptor, where the kappa agonist cyclazozine and the ''universal'' opioid agonist etorphine can induce upregulation in HEK293 cell cultures [25]. Several laboratories have reported an increase in D2 (but not D1) dopamine receptors after chronic agonist exposure [26][27][28][29].…”
Section: Discussionmentioning
confidence: 97%
“…(37) reported that a 24-h treatment with etorphine and cyclazocine significantly promoted maturation of rat KOPRs (rKOPRs), but treatment with U69,593 and salvinorin A did not, although all four agonists are cell-permeant and rKOPRs are not internalized and degraded following receptor activation. Thus, cell-permeant ligands showed differential abilities to act as pharmacological chaperones.…”
Section: Pharmacological Chaperone Effects Of Cell-permeant Ligandmentioning
confidence: 99%